INDIVIDUALLY ORIENTED INNOVATIVE EDUCATIONAL TECHNOLOGIES (Scientific journal of the Fergana State University, 2024)
The use of personality-oriented innovative pedagogical technologies and the development of professional training of future teachers, identifying the challenges facing their wide implementation in education and providing them with a specific project solution, as well as its justification on the basis of innovative pedagogical technologies.